Fulminant Amebic Colitis after Corticosteroid Therapy: A Systematic Review. - Debbie-Ann Shirley; Shannon Moonah (Public Library of Science (PLoS), 2016)
BACKGROUND:Amebic colitis, caused by intestinal infection with the parasite, Entamoeba histolytica, is a common cause of diarrhea worldwide. Fulminant amebic colitis is the most devastating complication of this infection, associated with both high mortality and morbidity. We conducted a review of the English literature to describe cases of fulminant amebic colitis associated with exposure to corticosteroid medications in order to identify the risk factors for poor outcome and determine difficulties in diagnosis and treatment. METHODOLOGY AND PRINCIPAL FINDINGS:Articles reporting severe and fulminant forms of amebic colitis between 1991 and 2016 were collected. 525 records were screened to identify 24 cases for qualitative analysis associated with corticosteroid use. Cases arose from areas of high endemicity or travel to such areas. Most cases (14 of 24, 58%) were given corticosteroids for initially misdiagnosed colitis, mainly inflammatory bowel, resulting in rapid progression of disease. Nearly half of all cases underwent surgical intervention, and 25% of cases died, despite all patients eventually receiving treatment with metronidazole. The odds of death did not differ significantly by prior misdiagnosis, co-morbidities, bowel perforation or need for surgery. CONCLUSIONS AND SIGNIFICANCE:Infection with E. histolytica should be considered prior to the administration of corticosteroids, in particular for patients residing in endemic areas or those with appropriate travel history, especially prior to the diagnosis of inflammatory bowel disease. The development of preventative and treatment interventions are needed to improve outcomes of fulminant disease.